In-situ polymerized functional polymer composite film, and preparation method and application thereof
Patent Information
- Application Number
- CN202610838926.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-11
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-06-11
AI Technical Summary
共轭微孔聚合物(CMP)因其兼具共轭骨架的电子传导能力与微孔结构的高比表面积,在分子识别与富集方面展现出独特优势,但其本征导电性较差,且成膜质量难以控制,限制了其在电化学传感中的直接应用
本发明提供的聚合物复合薄膜,通过使MXene纳米片嵌入式分散于4,4',4''-三(咔唑-9-基)三苯胺与N-(2-氨乙基)咔唑氢溴酸盐共聚形成的共轭微孔聚合物基体的三维微孔网络中,构筑了高效的三维导电通路,该结构设计有效抑制了MXene纳米片的自堆叠,充分暴露了其电化学活性位点,同时共轭微孔聚合物的多孔结构提供了丰富的传质通道和较大的比表面积,二者协同赋予了复合薄膜优异的电子传输能力与结构稳定性;该聚合物复合薄膜用作电化学传感器的敏感膜,利用共轭微孔聚合物对芳香族化合物的富集效应以及MXene纳米片的高电催化活性,可实现对邻硝基苯酚、间硝基苯酚和对硝基苯酚异构体的高灵敏度同时检测,具有良好的选择性、重现性和长期稳定性,在环境监测领域具有广阔的应用前景。
Smart Images

Figure CN122381522B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional polymer materials technology, and in particular to an in-situ polymerized functional polymer composite film, its preparation method, and its application. Background Technology
[0002] o-nitrophenol (o-NP), m-nitrophenol (m-NP), and p-nitrophenol (p-NP) are collectively known as nitrophenol isomers. All three are important chemical intermediates widely used in the production of fine chemicals such as explosives, pharmaceuticals, pesticides, and dyes. However, nitrophenol isomers exhibit high chemical stability and biotoxicity. Even at extremely low concentrations, their residues can enter natural water bodies through industrial wastewater discharge, causing persistent harm to aquatic ecosystems and potentially threatening human health through bioaccumulation in the food chain. The three nitrophenol isomers have highly similar structures and chemical properties, often coexisting in real-world environmental samples. Therefore, achieving simultaneous, rapid, and accurate detection of all three isomers has become a major technical challenge in analytical chemistry.
[0003] Currently, the main methods for detecting nitrophenol include high-performance liquid chromatography (HPLC), gas chromatography-mass spectrometry (GC-MS), and capillary electrophoresis. While these methods offer high sensitivity and accuracy, they generally suffer from drawbacks such as expensive instruments, complex operation, cumbersome sample pretreatment, and long detection cycles, making them unsuitable for rapid on-site detection. Electrochemical detection methods, due to their advantages of simple operation, rapid response, low cost, and ease of miniaturization, have become an important development direction for replacing traditional instrumental analysis. However, the development of electrochemical sensors for nitrophenol still faces key bottlenecks: the three isomers have similar redox potentials on traditional electrodes, easily leading to signal overlap and making selective differentiation difficult; simultaneously, the performance of the electrode surface modification material directly determines the sensor's sensitivity, stability, and anti-interference capability.
[0004] Against this backdrop, functional thin film materials have become crucial for enhancing the performance of electrochemical sensors. Conjugated microporous polymers (CMPs) exhibit unique advantages in molecular recognition and enrichment due to their combination of the electronic conductivity of a conjugated framework and the high specific surface area of a microporous structure. However, their poor intrinsic conductivity and difficulty in controlling film quality limit their direct application in electrochemical sensing. Two-dimensional materials such as MXene (e.g., Ti3C2T) are also relevant. xMXene possesses excellent metallic conductivity, abundant surface functional groups, and good hydrophilicity. However, the strong van der Waals forces between its layers make it prone to stacking and aggregation, leading to a decrease in effective specific surface area and making it difficult to fully utilize its conductivity and adsorption properties. Current research has attempted to combine CMP and MXene through physical blending or drop coating, but this method suffers from weak interfacial bonding, uneven dispersion, and poor film formation controllability, making it difficult to achieve synergistic enhancement of the two properties. Furthermore, the poor dispersibility of hydrophilic MXene in organic electrolytes further limits its application in electrochemical polymerization systems.
[0005] Therefore, how to design and construct organic-inorganic composite interfaces at the molecular level to achieve uniform composite and stable film formation of CMP and MXene, while simultaneously solving the problems of conductivity and structural stability, is a technical challenge that urgently needs to be overcome in the field of functional thin films. Summary of the Invention
[0006] The present invention aims to at least solve one of the aforementioned technical problems existing in the prior art. Therefore, one object of the present invention is to provide a polymer composite film.
[0007] The second objective of this invention is to provide a method for preparing such a polymer composite film.
[0008] The third objective of this invention is to provide an electrochemical sensor.
[0009] The fourth objective of this invention is to provide an electrochemical detection method for nitrophenol isomers.
[0010] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A first aspect of the present invention provides a polymer composite film comprising a conjugated microporous polymer matrix and MXene nanosheets; wherein the conjugated microporous polymer matrix is formed by copolymerization of 4,4',4''-tris(carbazole-9-yl)triphenylamine (TCTA) and N-(2-aminoethyl)carbazole hydrobromide (CzEA·HBr); and the MXene nanosheets are embedded and dispersed in a three-dimensional microporous network of the conjugated microporous polymer matrix.
[0011] In some embodiments of the present invention, the structural formula of the N-(2-aminoethyl)carbazole hydrobromide is shown in formula (I): Equation (Ⅰ); The MXene nanosheets are bonded to the N-(2-aminoethyl)carbazole hydrobromide via electrostatic or hydrogen bonding.
[0012] In some preferred embodiments of the present invention, the MXene nanosheets are bonded to the N-(2-aminoethyl)carbazole hydrobromide via electrostatic interaction.
[0013] In some embodiments of the present invention, the MXene nanosheets comprise Ti3C2T X , among which, T X It is selected from at least one of -OH, -F, and -O.
[0014] In some embodiments of the present invention, the N-(2-aminoethyl)carbazole hydrobromide is prepared by a method comprising the following steps: First, carbazole and a base are added to the solvent to deprotonate the carbazole; then, haloethylamine hydrochloride is added to carry out an N-alkylation reaction; after the reaction is completed, the liquid phase is collected by solid-liquid separation, and after removing the solvent, hydrobromic acid is added for acidification to obtain the N-(2-aminoethyl)carbazole hydrobromide.
[0015] In some embodiments of the present invention, the liquid-to-solid ratio of the solvent to carbazole is 100 mL: (25-40) g.
[0016] In some preferred embodiments of the present invention, the liquid-to-solid ratio of the solvent to carbazole is 100 mL: (30-37) g.
[0017] In some embodiments of the present invention, the solvent is selected from at least one of acetonitrile, N,N-dimethylformamide, dimethyl sulfoxide, and tetrahydrofuran.
[0018] In some preferred embodiments of the present invention, the solvent is acetonitrile.
[0019] In some embodiments of the present invention, the mass ratio of the alkali, carbazole and haloethylamine hydrochloride is (0.6-1.1): 1: (0.5-0.9).
[0020] In some preferred embodiments of the present invention, the mass ratio of the alkali, carbazole and haloethylamine hydrochloride is (0.7-1.0): 1: (0.6-0.8).
[0021] In some embodiments of the present invention, the alkali is selected from at least one of sodium hydroxide, sodium hydroxide, sodium hydride, potassium tert-butoxide, sodium tert-butoxide, and potassium carbonate.
[0022] In some preferred embodiments of the present invention, the alkali is sodium hydroxide.
[0023] In some embodiments of the present invention, the haloethylamine hydrochloride is selected from at least one of 2-chloroethylamine hydrochloride and 2-bromoethylamine hydrobromide.
[0024] In some preferred embodiments of the present invention, the haloethylamine hydrochloride is 2-chloroethylamine hydrochloride.
[0025] In some embodiments of the present invention, the deprotonation process is accompanied by stirring for 20-40 minutes.
[0026] In some embodiments of the present invention, the N-alkylation reaction further includes the use of a phase transfer catalyst; the mass ratio of the phase transfer catalyst to haloethylamine hydrochloride is 1:(7-11).
[0027] In some preferred embodiments of the present invention, the phase transfer catalyst comprises tetrabutylammonium bisulfate (TBAHS).
[0028] In some embodiments of the present invention, the acidification process is followed by purification and drying.
[0029] A second aspect of the present invention provides a method for preparing the polymer composite film described in the first aspect of the present invention, comprising the following steps: First, the MXene nanosheet suspension was mixed with N-(2-aminoethyl)carbazole hydrobromide for pre-assembly, and then 4,4',4''-tris(carbazole-9-yl)triphenylamine was added to form a mixed system. A three-electrode system is used, with the mixed system as the electrolyte, and the polymer composite film is formed on the surface of the working electrode by cyclic voltammetry.
[0030] Specifically, this invention uses N-(2-aminoethyl)carbazole hydrobromide as the functional monomer. CzEA·HBr is an electrically neutral ionic crystal that is charge balanced in the solid state but dissociates under solvent conditions, releasing positively charged CzEA-NH 3+ The cations are dispersed in the solution, while the bromide ions exist as free counter anions, CzEA-NH 3+ Cations pass through their positively charged -NH 3+ The side chains form electrostatic adsorption with negatively charged functional groups such as -OH, -F, and -O on the MXene surface, thereby anchoring the functional monomers on the MXene surface.
[0031] In some embodiments of the present invention, the content of MXene nanosheets in the MXene nanosheet suspension is 0.8-1.2 mg / mL.
[0032] In some preferred embodiments of the present invention, the content of MXene nanosheets in the MXene nanosheet suspension is 0.9-1.1 mg / mL.
[0033] In some embodiments of the present invention, the content of N-(2-aminoethyl)carbazole hydrobromide in the MXene nanosheet suspension is 0.8-1.2 mmol / L.
[0034] In some preferred embodiments of the present invention, the content of N-(2-aminoethyl)carbazole hydrobromide in the MXene nanosheet suspension is 0.9-1.1 mmol / L.
[0035] In some embodiments of the present invention, the MXene nanosheet suspension is obtained by a method comprising the following steps: MXene powder was dispersed in an organic solvent and ultrasonically exfoliated to obtain the MXene nanosheet suspension.
[0036] In some embodiments of the present invention, the organic solvent comprises dichloromethane and acetonitrile in a volume ratio of (4-5):1.
[0037] Specifically, MXene is a hydrophilic material that is generally well dispersed in aqueous phase and can also be stably dispersed in some organic solvents (such as acetonitrile, N,N-dimethylformamide, and N-methylpyrrolidone). However, many of these organic solvents are not effective in subsequent electropolymerization. In this invention, MXene (powder) is dispersed in a common electropolymerization mixture of dichloromethane and acetonitrile with a volume ratio of (4-5):1. In this solvent system, dichloromethane is responsible for dissolving organic matter, while acetonitrile is responsible for dispersing MXene and organic matter. This not only disperses MXene well to a certain extent but also serves as an electrolyte solution for subsequent electropolymerization, avoiding the steps of solvent replacement or adding other solvents and simplifying the preparation process.
[0038] In some embodiments of the present invention, the pre-assembly temperature is 36-54°C and the time is 10-15 hours.
[0039] In some preferred embodiments of the present invention, the pre-assembly temperature is 40-50°C and the time is 10-12 hours.
[0040] In some embodiments of the invention, the pre-assembly process is aided by stirring.
[0041] In some embodiments of the present invention, the pre-assembly is carried out under closed conditions.
[0042] In some embodiments of the present invention, the molar ratio of 4,4',4''-tris(carbazole-9-yl)triphenylamine to N-(2-aminoethyl)carbazole hydrobromide is 1:(0.8-1.2).
[0043] In some preferred embodiments of the present invention, the molar ratio of 4,4',4''-tris(carbazole-9-yl)triphenylamine to N-(2-aminoethyl)carbazole hydrobromide is 1:(0.9-1.1).
[0044] In some embodiments of the present invention, the electrolyte further includes an added co-electrolyte; the molar ratio of the co-electrolyte to 4,4',4''-tris(carbazole-9-yl)triphenylamine is (80-120):1.
[0045] In some preferred embodiments of the present invention, the molar ratio of the electrolyte to 4,4',4''-tris(carbazole-9-yl)triphenylamine is (90-110):1.
[0046] In some embodiments of the present invention, the electrolyte comprises tetrabutylammonium hexafluorophosphate (TBAPF6).
[0047] In some embodiments of the present invention, in the three-electrode system, the working electrode is selected from a glassy carbon electrode (GCE) or an ITO electrode; the counter electrode includes a platinum wire electrode; and the reference electrode includes Ag / Ag. + Electrode and Ag / AgCl electrode.
[0048] In some embodiments of the present invention, the voltage range of the cyclic voltammetric electropolymerization is -0.5 to 1.2 V, the scan rate is 80-120 mV / s, and the number of cycles is 2-10.
[0049] In some preferred embodiments of the present invention, the voltage range of the cyclic voltammetric electropolymerization is -0.5 to 1.2 V, the scan rate is 90-110 mV / s, and the number of cycles is 2-6.
[0050] In some embodiments of the present invention, the cyclic voltammetric electropolymerization is followed by a cleaning and drying process.
[0051] In some embodiments of the present invention, the cleaning agent includes dichloromethane.
[0052] In some embodiments of the present invention, the drying method is cold air drying.
[0053] A third aspect of the present invention provides an electrochemical sensor, comprising an electrode substrate and a sensitive membrane disposed on the surface of the electrode substrate, wherein the sensitive membrane is the polymer composite film described in the first aspect of the present invention.
[0054] A fourth aspect of the present invention provides an electrochemical detection method for nitrophenol isomers, wherein the nitrophenol isomers include at least one of o-nitrophenol, m-nitrophenol, and p-nitrophenol; the electrochemical detection method includes the following steps: A three-electrode system is used, with the electrochemical sensor described in the third aspect of the present invention as the working electrode and the sample to be tested as the electrolyte. After potential enrichment, the nitrophenol isomer in the sample to be tested is detected by differential pulse voltammetry.
[0055] In some embodiments of the present invention, the sample to be tested includes an environmental water sample.
[0056] In some preferred embodiments of the present invention, the sample to be tested includes river water, lake water, tap water or industrial wastewater.
[0057] It should be noted that the samples to be tested are not limited to environmental water samples, but may also include other liquid samples, such as food and beverages.
[0058] In some embodiments of the present invention, the enrichment potential of the potential enrichment is -1.0 to -0.5V.
[0059] In some preferred embodiments of the present invention, the enrichment potential of the potential enrichment is -1.0 to -0.8V.
[0060] In some embodiments of the present invention, the enrichment time of the potential enrichment is 120-180s.
[0061] In some preferred embodiments of the present invention, the enrichment time of the potential enrichment is 150-180s.
[0062] In some embodiments of the present invention, the electrochemical detection method for nitrophenol isomers can simultaneously detect o-nitrophenol, m-nitrophenol and p-nitrophenol in the sample to be tested.
[0063] In some embodiments of the present invention, the electrochemical detection method for the nitrophenol isomers has a detection limit of 0.026 µmol / L for o-nitrophenol, a detection limit of 0.0252 µmol / L for m-nitrophenol, and a detection limit of 0.033 µmol / L for p-nitrophenol.
[0064] Specifically, the electrochemical detection method for nitrophenol isomers provided by the present invention first performs potential enrichment under a set external constant potential, so that the nitrophenol isomers in the sample to be tested are adsorbed and enriched on the sensitive membrane surface of the working electrode by the electric field force, thereby increasing the concentration of the analyte on the electrode surface, amplifying the detection current, and reducing the detection limit. Then, the quantification is performed by differential pulse voltammetry.
[0065] Compared with the prior art, the beneficial effects of the present invention are: The polymer composite film provided by this invention constructs a highly efficient three-dimensional conductive pathway by embedding MXene nanosheets within a three-dimensional microporous network of a conjugated microporous polymer matrix formed by copolymerizing 4,4',4''-tris(carbazole-9-yl)triphenylamine and N-(2-aminoethyl)carbazole hydrobromide. This structural design effectively suppresses the self-stacking of MXene nanosheets and fully exposes their electrochemical active sites. Simultaneously, the porous structure of the conjugated microporous polymer provides abundant mass transfer channels and a large specific surface area. These two factors synergistically endow the composite film with excellent electron transport capabilities and structural stability. When used as the sensitive membrane of an electrochemical sensor, this polymer composite film utilizes the enrichment effect of the conjugated microporous polymer on aromatic compounds and the high electrocatalytic activity of the MXene nanosheets to achieve highly sensitive simultaneous detection of o-nitrophenol, m-nitrophenol, and p-nitrophenol isomers. It exhibits good selectivity, reproducibility, and long-term stability, and has broad application prospects in the field of environmental monitoring.
[0066] The polymer composite film preparation method provided by the present invention adopts cyclic voltammetric electropolymerization, which realizes the uniform composite of MXene nanosheets and conjugated microporous polymer matrix at the molecular level. The process is simple and controllable. Attached Figure Description
[0067] Figure 1 This is a schematic diagram of the preparation process of the polymer composite film in Example 1; Figure 2 The 1H NMR spectrum of N-(2-aminoethyl)carbazole hydrobromide prepared in Example 1; Figure 3 The electropolymerization process of the composite films in Comparative Examples 3(a), 1(b), and 2(c) is shown. Figure 4 The cyclic voltammetry curves for continuous cycles in Example 1 and Comparative Example 3; Figure 5 XPS spectrum of the polymer composite film of Example 1; Figure 6 The FTIR spectra of the polymer composite film of Example 1, MXene, and the composite film of Comparative Example 3 are shown below. Figure 7 SEM images of the composite film (a) of Comparative Example 3 and the polymer composite film (b) of Example 1; Figure 8 The image shows the EDS spectrum of the polymer composite film in Example 1. Figure 9 Cyclic voltammetry diagrams of the polymer composite film modified electrode in Example 1 and the composite film modified electrodes in Comparative Examples 1-3 are shown. Figure 10Electrochemical impedance spectroscopy of the polymer composite film modified electrode in Example 1 and the composite film modified electrodes in Comparative Examples 1-3; Figure 11 The DPV curves of the polymer composite film modified electrode in Example 1 for individual o-NP, m-NP, and p-NP are shown. Figure 12 DPV curves of bare glassy carbon electrode, polymer composite film modified electrode in Example 1, and composite film modified electrode in Comparative Examples 1-3 for o-NP / m-NP / p-NP mixtures; Figure 13 The cyclic voltammetry curves of the polymer composite film modified electrode in Example 1 in a mixture of three nitrophenol isomers are shown below. Figure 14 The electrochemical reaction mechanism of nitrophenol on the polymer composite film of Example 1; Figure 15 The results show the optimization of key experimental conditions for polymer composite films used in the detection of nitrophenol isomers; Figure 16 The DPV response curves and Ipa-concentration standard curves of the polymer composite film in Example 1 with different concentrations of nitrophenol isomers in PBS solution (pH=7.4) are shown. Figure 17 The repeatability evaluation results of the polymer composite film used in Example 1 for the detection of o-NP(a), m-NP(b) and p-NP(c) are shown. Figure 18 The results show the anti-interference evaluation of the polymer composite film used in Example 1 for the detection of o-NP(a), m-NP(b) and p-NP(c). Detailed Implementation
[0068] The present invention will be further described in detail below with reference to specific accompanying drawings and embodiments. Unless otherwise specified, the raw materials, reagents, or apparatus used in the embodiments and comparative examples are all available from conventional commercial sources or can be obtained by existing technical methods. Unless otherwise specified, the experimental or testing methods are conventional methods in the art.
[0069] Figure 1 This is a schematic diagram of the preparation process of the polymer composite film in Example 1. Figure 1 It is known that the preparation of this polymer composite film uses N-(2-aminoethyl)carbazole hydrobromide (CzEA·HBr) as a functional monomer. Its molecular structure contains an electroactive carbazole group that can be used for subsequent polymerization, and an amino side chain that can carry a positive charge under solvent conditions. Under heating conditions, CzEA·HBr utilizes the positive charge of its amino side chain and the hydrophilic MXene (Ti3C2T) xElectrostatic assembly of negatively charged functional groups on the surface of MXene nanosheets is achieved, anchoring them to the surface and modifying the MXene nanosheets. This solves the problem of the difficulty in uniformly dispersing and depositing hydrophilic MXene in organic electrolytes. Subsequently, the crosslinking monomer 4,4',4''-tris(carbazole-9-yl)triphenylamine (TCTA) and the coelectrolyte tetrabutylamine hexafluorophosphate (TBAPF6) are added to the system. Cyclic voltammetric scanning polymerization is performed in a three-electrode system. With the increase of the number of cycles, a brownish polymer composite film is formed on the surface of the working electrode (GCE) with MXene nanosheets embedded and dispersed in a three-dimensional microporous network of a conjugated microporous polymer matrix formed by in-situ copolymerization of TCTA and CzEA·HBr. The following will combine... Figure 1 The preparation of the polymer composite film in Example 1 is described below: Example 1 This embodiment prepares a polymer composite film using the following steps: S11. At room temperature, 11.51 g of sodium hydroxide and 13.37 g of carbazole were added to a round-bottom flask containing 40 mL of anhydrous acetonitrile and stirred for 30 min to convert the carbazole into the corresponding anionic form. 1.08 g of phase transfer catalyst tetrabutylammonium hydrogen sulfate and 9.97 g of 2-chloroethylamine hydrochloride were added sequentially to the mixture. The reaction system was placed in a 90 °C oil bath and continuously heated under reflux with stirring for 24 h to carry out the N-alkylation reaction. After the reaction was completed, the mixture was cooled to room temperature, and the insoluble solids (mainly inorganic salts) were removed by filtration. The acetonitrile solvent was removed by rotary evaporation under reduced pressure to obtain a residual oily substance. Excess hydrobromic acid (HBr) was added to the residual oily substance for acidification, causing the product to precipitate as hydrobromide. The product was then purified by recrystallization multiple times with ethanol, and finally dried under vacuum to obtain the off-white solid product N-(2-aminoethyl)carbazole hydrobromide (CzEA·HBr). S12, MXene powder (Ti3C2T) x The MXene was dispersed in a mixed solution of dichloromethane and acetonitrile (4:1, v / v) and ultrasonically exfoliated to obtain a uniform suspension with a content of 1 mg / mL. S21. The suspension and N-(2-aminoethyl)carbazole hydrobromide were added to the electrolytic cell to make the N-(2-aminoethyl)carbazole hydrobromide content 1 mmol / L. The mixture was sealed and stirred at 45°C for 12 h to allow the monomer molecules to be adsorbed and anchored on the MXene surface through electrostatic interaction, thus obtaining modified MXene. S31. Add 4,4',4''-tris(carbazole-9-yl)triphenylamine (1 mmol / L) and the co-electrolyte tetrabutylamine hexafluorophosphate (0.1 mol / L) to the system obtained in step S21. Use a three-electrode system with a glassy carbon electrode as the working electrode and a platinum wire as the counter electrode. Ag / Ag +As a reference electrode, electropolymerization was performed using cyclic voltammetry scanning with a voltage range of -0.5 to 1.2 V, a scan rate of 100 mV / s, and 8 cycles. After polymerization, the electrode surface was rinsed with dichloromethane to remove physically adsorbed monomers and dried with cold air to prevent hot air from oxidizing MXene, resulting in a brown polymer composite film uniformly deposited on the working electrode surface.
[0070] Figure 2 The image shows the 1H NMR spectrum of N-(2-aminoethyl)carbazole hydrobromide prepared in Example 1. Figure 2 It can be seen that N-(2-aminoethyl)carbazole hydrobromide was successfully synthesized, and after recrystallization, it had high purity, no obvious raw material residue, and its molecular structure was consistent with the design, which can be used for the preparation of polymer composite films.
[0071] Comparative Example 1 A composite film was prepared in this comparative example, and the steps are as follows: 1) In an electrolytic cell, 4,4',4''-tris(carbazole-9-yl)triphenylamine (1 mmol / L) and the co-electrolyte tetrabutylamine hexafluorophosphate (0.1 mol / L) were added to a mixed solution of dichloromethane and acetonitrile (4:1, v / v); 2) A three-electrode system is adopted, with a glassy carbon electrode as the working electrode and a platinum wire as the counter electrode, Ag / Ag + As a reference electrode, electropolymerization was performed using cyclic voltammetry with a voltage range of -0.5 to 1.2 V, a scan rate of 100 mV / s, and 8 cycles. After polymerization, the electrode surface was rinsed with dichloromethane to remove physically adsorbed monomers, and then dried to obtain a composite film deposited on the working electrode surface.
[0072] Comparative Example 2 A composite film was prepared in this comparative example, and the steps are as follows: 1) In an electrolytic cell, N-(2-aminoethyl)carbazole hydrobromide (1 mmol / L) and the co-electrolyte tetrabutylammonium hexafluorophosphate (0.1 mol / L) were added to a mixed solution of dichloromethane and acetonitrile (4:1, v / v); 2) A three-electrode system is adopted, with a glassy carbon electrode as the working electrode and a platinum wire as the counter electrode, Ag / Ag + As a reference electrode, electropolymerization was performed using cyclic voltammetry with a voltage range of -0.5 to 1.2 V, a scan rate of 100 mV / s, and 8 cycles. After polymerization, the electrode surface was rinsed with dichloromethane to remove physically adsorbed monomers, and then dried to obtain a composite film deposited on the working electrode surface.
[0073] Comparative Example 3 A composite film was prepared in this comparative example, and the steps are as follows: 1) In an electrolytic cell, N-(2-aminoethyl)carbazole hydrobromide (1 mmol / L), 4,4',4''-tris(carbazole-9-yl)triphenylamine (1 mmol / L) and the co-electrolyte tetrabutylamine hexafluorophosphate (0.1 mol / L) were added to a mixed solution of dichloromethane and acetonitrile (4:1, v / v); 2) A three-electrode system is adopted, with a glassy carbon electrode as the working electrode and a platinum wire as the counter electrode, Ag / Ag + As a reference electrode, electropolymerization was performed using cyclic voltammetry with a voltage range of -0.5 to 1.2 V, a scan rate of 100 mV / s, and 8 cycles. After polymerization, the electrode surface was rinsed with dichloromethane to remove physically adsorbed monomers, and then dried to obtain a composite film deposited on the working electrode surface.
[0074] Characterization and performance testing 1. Analyze the electropolymerization process of the composite films in Example 1 and Comparative Examples 1-3: Figure 3 For the electropolymerization process of the composite films in Comparative Examples 3(a), 1(b), and 2(c), by... Figure 3 It can be seen that when only the crosslinking monomer TCTA was added in Comparative Example 1 and only the functional monomer CzEA·HBr was added in Comparative Example 2, the two monomers had their own oxidation peak potentials. In Comparative Example 3, both TCTA and CzEA·HBr were added, and the oxidation peak potentials of the two monomers appeared in the cyclic voltammetry curve, indicating that the two monomers underwent in-situ co-electropolymerization on the electrode surface to form a conjugated microporous polymer.
[0075] Figure 4 The cyclic voltammetry curves for continuous cycles in Example 1 and Comparative Example 3 are shown below. Figure 4 In Figure (a), the cyclic voltammetry curves for 7 consecutive cycles in Comparative Example 3 are shown. Figure 4 (b) shows a comparison of the cyclic voltammetry curves for six consecutive cycles in Example 1 and Comparative Example 3. Figure 4 As can be seen, in Example 1 and Comparative Example 3, the redox current gradually increased with the increase of the number of scan cycles, indicating that the conductive polymer film was growing on the electrode surface. Compared with Comparative Example 3 without MXene, the addition of MXene in Example 1 significantly increased the polymerization current and slightly decreased the oxidation potential, proving that MXene was successfully embedded in the polymer film and formed a conductive channel, thereby improving the conductivity of the polymer film.
[0076] 2. Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, scanning electron microscopy, and energy dispersive spectroscopy were performed on the MXene and polymer composite film in Example 1 and the composite film in Comparative Example 3: Figure 5 The XPS spectrum of the polymer composite film in Example 1 is shown below. Figure 5 It can be seen that the polymer composite film contains both the conjugated microporous polymer (N) composed of TCTA and CzEA·HBr and the characteristic element of MXene (Ti), proving that the two are successfully composited and that each element retains its own characteristic chemical valence state.
[0077] Figure 6 The FTIR spectra of the polymer composite film of Example 1, MXene, and the composite film of Comparative Example 3 are shown below. Figure 6 It can be seen that the polymer composite film contains a conjugated microporous polymer composed of TCTA and CzEA·HBr, and MXene-anchored -NH 3+ Peak displacement (3273cm) -1 up to 3271cm -1 This indicates that there is an interaction (electrostatic interaction / hydrogen bonding) between the conjugated microporous polymer and MXene, which is not a simple physical mixture, and a molecular-level composite is achieved.
[0078] Figure 7 The images are SEM images of the composite film (a) of Comparative Example 3 and the polymer composite film (b) of Example 1. Figure 7 It can be seen that the addition of MXene optimizes the microstructure of the conjugated microporous polymer and inhibits the dense aggregation of the polymer. At the same time, MXene itself does not stack, forming a porous structure in which the polymer encapsulates MXene.
[0079] Figure 8 The image shows the EDS spectrum of the polymer composite film in Example 1, wherein... Figure 8 (a) in the image is the EDS full spectrum. Figure 8 (b) in the diagram is the surface distribution map of element C. Figure 8 (c) in the diagram is the surface distribution map of element N. Figure 8 (d) in the diagram represents the surface distribution of element O. Figure 8 (e) in the diagram represents the surface distribution of Ti elements. Figure 8 As can be seen, MXene nanosheets are embedded in the polymer structure, and C and N elements are present on the sheets, indicating polymer growth. The energy spectrum of Ti also shows the color of small pieces of MXene nanosheets, which is not obvious in the SEM image, indicating that they are completely encapsulated by the polymer. This means that the polymer provides growth sites for the conjugated microporous polymer matrix, and the polymer grows along the surface of MXene, forming a unique embedded structure.
[0080] 3. Compare the conductivity, electron transfer capability, and p-nitrophenol isomer recognition capability of the bare glassy carbon electrode (GCE), the polymer composite film modified electrode in Example 1, and the composite film modified electrodes in Comparative Examples 1-3: 1) Cyclic voltammetry was used, with [Fe(CN)6] as the reference value. 3- / 4- Redox pairs were used as probes to evaluate the electron transfer rate on the electrode surface: A three-electrode system was constructed, with the working electrodes being a bare glassy carbon electrode, the polymer composite film modified electrode in Example 1, and the composite film modified electrode in Comparative Examples 1-3, respectively. The reference electrode was an Ag / AgCl electrode, and the counter electrode was a platinum wire. The electrolyte was a 0.01mol / L PBS solution containing 5.0mmol / L K3[Fe(CN)6] / K4[Fe(CN)6] (1:1, v / v) + 0.1mol / L KCl. The scan rate was 50mV / s, the voltage range was 0-0.6V, and cyclic voltammetry curves were collected. 2) In the same three-electrode system and electrolyte as in 1), the electron transfer resistance at the electrode / electrolyte interface was quantitatively evaluated by detecting the impedance of the electrodes at different frequencies. The EIS test parameters were set to a frequency of 1×10⁻⁶. -1 Hz-1×10 5 Hz, AC amplitude is 5mV; 3) Using differential pulse voltammetry, with the polymer composite film modified electrode from Example 1 as the working electrode, a PBS buffer solution (pH=7.4) containing o-nitrophenol (o-NP), m-nitrophenol (m-NP), and p-nitrophenol (p-NP) was prepared. The DPV parameters were set as follows: pre-enrichment (it method, potential of -1.0V, enrichment time of 180s), scan voltage of -0.5-0.5V, and pulse amplitude of 50mV. The DPV curve was then acquired. 4) Using differential pulse voltammetry, a mixed PBS solution (pH=7.4) containing equal concentrations of o-NP, m-NP, and p-NP was prepared. Using a bare glassy carbon electrode, the polymer composite film modified electrode from Example 1, and the composite film modified electrodes from Comparative Examples 1-3 as working electrodes, the DPV parameters were measured according to the same procedure in 3). Figure 9 The cyclic voltammograms are for the polymer composite film modified electrode in Example 1 and the composite film modified electrodes in Comparative Examples 1-3, respectively. Figure 9 It can be seen that the oxidation peak current of the polymer composite film modified electrode in Example 1 is significantly greater than that of the other electrodes, and the peak spacing between the oxidation peak and the reduction peak is the smallest. This indicates that the polymer composite film in Example 1 significantly improves the electron transfer rate on the electrode surface and has the best conductivity. In contrast, the composite film in Comparative Example 3 has the worst conductivity because the electron transfer is hindered by the side chain effect added to the amorphous network of poly(4,4',4''-tris(carbazole-9-yl)triphenylamine) (PTCTA) after the copolymerization of the two monomers.
[0081] Figure 10 The electrochemical impedance spectroscopy (EIS) spectra of the polymer composite film modified electrode in Example 1 and the composite film modified electrodes in Comparative Examples 1-3 are obtained from... Figure 10It can be seen that the diameter of the capacitive arc corresponds to the charge transfer resistance R. ct In Example 1, the capacitive arc diameter of the polymer composite film modified electrode is almost negligible, indicating that after the conjugated microporous polymer matrix formed by the copolymerization of TCTA and CzEA·HBr is modified by co-deposition of MXene, the current response is greatly improved due to the good conductivity of MXene and its embedding in the three-dimensional microporous network structure of the matrix, which promotes electron transfer at the electrode interface and causes the resistance of the polymer composite film to decrease sharply.
[0082] Figure 11 The DPV curves for the polymer composite film modified electrode in Example 1 for individual o-NP, m-NP, and p-NP are shown below. Figure 11 It can be seen that the polymer composite film modified electrode in Example 1 showed obvious single oxidation peaks for o-NP, m-NP and p-NP on the curves, and the potentials of each oxidation peak were significantly different. This indicates that the polymer composite film has an independent electrocatalytic oxidation recognition ability for each nitrophenol isomer, which lays the foundation for the simultaneous detection of mixtures.
[0083] Figure 12 The DPV curves of the bare glassy carbon electrode, the polymer composite film modified electrode in Example 1, and the composite film modified electrodes in Comparative Examples 1-3 are shown below for the o-NP / m-NP / p-NP mixture. Figure 12 It can be seen that the oxidation peaks of the three nitrophenol isomers overlap and cannot be distinguished in the curves of the bare glassy carbon electrode and the composite film modified electrode in Comparative Example 1. In contrast, the curve of the polymer composite film modified electrode in Example 1 shows three clearly separated oxidation peaks with a large peak spacing and a significantly higher oxidation peak current than other electrodes. This indicates that the polymer composite film in Example 1 solves the signal overlap problem of traditional electrodes for detecting nitrophenol isomer mixtures, and achieves high selectivity and high sensitivity for simultaneous detection of the three isomers. It is an excellent electrochemical sensing material for nitrophenol.
[0084] 4. Investigating the electrochemical reaction mechanism of nitrophenol on the polymer composite film in Example 1: Cyclic voltammetry was used, with the polymer composite film modified electrode in Example 1 as the working electrode. The electrolyte was a 100 µmol / L PBS buffer solution of o-NP, m-NP, and p-NP (pH=7.4). The voltage range was -1.3 to 0.5 V, the scan rate was 100 mV / s, and multiple scans were performed continuously. Cyclic voltammetric curves were collected, and based on the characteristics of the cyclic voltammetric curves, the molecular structure of nitrophenol, and the electrochemical redox reaction rules, combined with relevant reports, the following deductions were made: Figure 13 The cyclic voltammetry curves for the polymer composite film modified electrode in Example 1 are shown below, in a mixture of three nitrophenol isomers. Figure 13It can be seen that m-NP and p-NP show a pair of obvious redox reversible peaks (O1 / R1, O2 / R2) in the curve, while o-NP only shows a single oxidation peak (O). Moreover, the peak shape and peak potential do not change significantly after continuous scanning. This indicates that the electrocatalytic reaction of the polymer composite film in Example 1 on m-NP and p-NP is a reversible redox reaction, while the reaction on o-NP is an irreversible oxidation reaction. Furthermore, the electrocatalytic performance of the film has good stability and no performance decay after continuous reaction.
[0085] Figure 14 The electrochemical reaction mechanism of nitrophenol on the polymer composite film of Example 1 is as follows: Figure 14 It can be seen that for m-NP and p-NP, the nitro group (-NO2) is first reduced to hydroxylamine (-NHOH) through a four-electron and four-proton transfer. Then, the hydroxylamine group undergoes a reversible redox reaction with the nitroso group (-NO) through a two-electron and two-proton transfer, corresponding to the O1 / R1 and O2 / R2 peaks in the cyclic voltammetry curve. For o-NP, due to the steric hindrance effect of the nitro group adjacent to the phenolic hydroxyl group in the molecular structure, only the irreversible oxidation reaction of the phenolic hydroxyl group through a proton and electron transfer occurs, corresponding to the single O peak in the cyclic voltammetry curve.
[0086] 5. Optimization of key experimental conditions for the detection of nitrophenol isomers: Differential pulse voltammetry was used, with a mixture of o-NP, m-NP, and p-NP as the detection target. The experimental conditions were changed using a single variable method, and the oxidation peak currents of the three isomers under each condition were recorded. The condition corresponding to the maximum current was taken as the optimal condition. Among them: 1) Optimization of enrichment time: With the enrichment potential fixed at -1.0V, MXene concentration at 1mg / mL, and polymerization cycle at 6 cycles, the enrichment time was varied (60-240), and the oxidation peak current was tested and recorded. 2) Optimization of enrichment potential: With the enrichment time fixed at 180s, MXene concentration at 1mg / mL, and polymerization cycle at 6 cycles, the enrichment potential was varied (-1~0.5V), and the oxidation peak current was tested and recorded. 3) Optimization of MXene nanosheet concentration: With the enrichment time fixed at 180s, enrichment potential at 1.0V, and polymerization cycle at 6 cycles, composite films with different MXene nanosheet contents were prepared by changing the concentration of MXene nanosheet suspension (0.5-2.0mg / mL), and the oxidation peak current was tested and recorded. 4) Optimization of polymerization cycle number: With a fixed enrichment time of 180 s, enrichment potential of -1.0 V, and MXene concentration of 1 mg / mL, composite films of different thicknesses were prepared by varying the number of polymerization cycles (5-10 cycles), and the oxidation peak current was tested and recorded. Figure 15 The results show the optimization of key experimental conditions for the use of polymer composite films in the detection of nitrophenol isomers. Figure 15 In the figures (a), (b), (c), and (d), the optimized results for enrichment time, enrichment potential, MXene nanosheet concentration, and polymerization number are respectively derived from... Figure 15 It can be seen that when the enrichment time is 0-180s, the oxidation peak current increases significantly with time, the current growth slows down after 180s, and the current begins to decrease after 240s, that is, the optimal enrichment time is 180s; the current reaches its maximum value when the enrichment potential is -1.0V, and the current decreases rapidly from -1.0V to 0.5V, that is, the optimal enrichment potential is -1.0V; when the MXene nanosheet concentration is 0.5-1.0mg / mL, the current increases significantly with the increase of concentration, the current reaches its maximum value at 1.0mg / mL, and the current gradually decreases from 1.0-2.0mg / mL, that is, the optimal MXene nanosheet concentration is 1mg / mL; when the number of polymerization cycles is 5-6, the current increases significantly with the increase of the number of cycles, the current reaches its maximum value at 6 cycles, and the current gradually decreases from 6-10 cycles, that is, the optimal number of polymerization cycles is 6 cycles. Therefore, the optimal conditions for an electrochemical sensor using a polymer composite film as the sensitive membrane to detect nitrophenol isomers are: enrichment potential -1.0V, enrichment time 180s, MXene nanosheet preparation concentration 1mg / mL, and polymerization cycle 6. Under these conditions, the detection signal is strongest and the sensitivity is highest.
[0087] 6. Verification of the performance of the polymer composite film for quantitative detection of nitrophenol isomers: A series of o-NP, m-NP, and p-NP single PBS solutions of different concentrations (concentration range 0.1-150 µmol / L) were prepared. Differential pulse voltammetry was used, with the polymer composite film modified electrode in Example 1 as the working electrode. DPV tests were performed under optimal detection conditions, and the oxidation peak current (Io) at each concentration was recorded. pa ), draw I pa - The concentration standard curve was fitted using linear regression to obtain a linear equation, and the limit of detection (LOD) was calculated according to the formula LOD = 3σ / S, where σ is the limit of detection obtained from 20 measurements of the blank solution. pa The relative standard deviation, S, is the slope of the calibration curve described above: Figure 16 The DPV response curves and Ig values of the polymer composite film in Example 1 with different concentrations of nitrophenol isomers in pure PBS solution are shown. pa -Concentration standard curve, where. Figure 16 In the figures (a), (b), and (c), the DPV response curves of the polymer composite film of Example 1 at different concentrations of o-NP, m-NP, and p-NP in pure PBS solution are shown, respectively. Figure 16 In the diagram, (d), (e), and (f) are the I values corresponding to (a), (b), and (c), respectively. pa -Concentration standard curve, from Figure 16It can be seen that as the concentration of nitrophenol isomers increases from 0.1 µmol / L to 150 µmol / L, the DPV oxidation peak currents corresponding to the three isomers all show a significant linear increasing trend, and the peak potentials do not shift significantly, proving that the linear relationship between concentration and current is good. Calculations show that the detection limits for o-NP are as low as 0.026 µmol / L, m-NP is 0.052 µmol / L, and p-NP is 0.033 µmol / L.
[0088] 7. Evaluation of the reproducibility of the polymer composite film for the detection of nitrophenol isomers: Differential pulse voltammetry was used, with the electrode modified with the polymer composite film from Example 1. Under optimal conditions, multiple repeated detections were performed on o-NP / m-NP / p-NP solutions of the same concentration. The reproducibility curve was plotted with the number of detections on the x-axis and the oxidation peak current on the y-axis. Figure 17 The repeatability evaluation results of the polymer composite film used in Example 1 for the detection of o-NP(a), m-NP(b), and p-NP(c) are presented by... Figure 17 It can be seen that after multiple detections, the oxidation peak currents of o-NP, m-NP, and p-NP did not fluctuate significantly, and the data points were highly concentrated. This indicates that the electrochemical sensor using polymer composite film as the sensitive membrane has excellent reproducibility for the detection of the three nitrophenol isomers. The composite film on the electrode surface has high stability and its performance does not significantly decay after multiple detections, making it suitable for continuous batch detection.
[0089] 8. Evaluation of the anti-interference performance of polymer composite films for the detection of nitrophenol isomers: Prepare a mixed PBS solution containing equal concentrations of o-NP / m-NP / p-NP as a blank detection solution, test and record the oxidation peak current (I0), and add common potential interfering substances (K) to the blank detection solution. + Mg 2+ Al 3+ Ca 2+ Ba 2+ Zn 2+ The oxidation peak current (I) of phenol, oxalic acid, nitrobenzene (NB), and 4-iodophenol (4-IodoPhenol) was measured after adding the interfering substances. The relative signal values were obtained after normalization. A bar chart of the interference effect was plotted with the type of interfering substance as the x-axis and the normalized intensity as the y-axis. Figure 18 The results of the anti-interference evaluation of the polymer composite film used for o-NP(a), m-NP(b), and p-NP(c) detection in Example 1 are presented by... Figure 18It can be seen that after adding various inorganic ions and organic interfering substances, the oxidation peak current of the three nitrophenol isomers did not change significantly. When the interfering substances were present, the oxidation peaks of the three nitrophenol isomers remained clearly separated, without peak shift or overlap, indicating that their anti-interference ability was good.
[0090] Application examples To evaluate the applicability of the polymer composite membrane in Example 1 for real water sample analysis, lake water and tap water from South China Normal University were collected and filtered. The pH of the filtrate was adjusted to 7.4 using PBS buffer solution. The standard addition method was used, with 100 µmol / L of nitrophenol isomers added to each of the two water samples for determination. The results are shown in Tables 1 and 2. The recoveries were both between 93% and 101%, indicating that the electrochemical sensor is suitable for the simultaneous detection of nitrophenol isomers in real water samples. Furthermore, the electrochemical sensor results were compared with HPLC results to verify the accuracy of the method. The recovery and comparison results show that the polymer composite membrane provided by this invention is expected to be an effective material for the determination of nitrophenol in real water samples.
[0091] Table 1. Detection results of nitrophenol in tap water using electrochemical sensors and HPLC.
[0092] Table 2. Detection results of nitrophenol in lake water by electrochemical sensor and HPLC
[0093] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.
Claims
1. A polymer composite film, characterized in that, The invention comprises a conjugated microporous polymer matrix and MXene nanosheets; wherein the conjugated microporous polymer matrix is formed by copolymerization of 4,4',4''-tris(carbazole-9-yl)triphenylamine and N-(2-aminoethyl)carbazole hydrobromide; the MXene nanosheets are embedded and dispersed in the three-dimensional microporous network of the conjugated microporous polymer matrix; the MXene nanosheets and the N-(2-aminoethyl)carbazole hydrobromide are bonded together by electrostatic or hydrogen bonding.
2. The polymer composite film according to claim 1, characterized in that, The structural formula of the N-(2-aminoethyl)carbazole hydrobromide is shown in formula (Ⅰ): Equation (Ⅰ).
3. The polymer composite film according to claim 1, characterized in that, The MXene nanosheets include Ti3C2T X , among which, T X It is selected from at least one of -OH, -F, and -O.
4. The method for preparing the polymer composite film according to any one of claims 1-3, characterized in that, Includes the following steps: First, the MXene nanosheet suspension was mixed with N-(2-aminoethyl)carbazole hydrobromide for pre-assembly, and then 4,4',4''-tris(carbazole-9-yl)triphenylamine was added to form a mixed system. A three-electrode system is used, with the mixed system as the electrolyte, and the polymer composite film is formed on the surface of the working electrode by cyclic voltammetry.
5. The preparation method according to claim 4, characterized in that, The MXene nanosheets in the suspension contain 0.8-1.2 mg / mL; And / or, the content of the N-(2-aminoethyl)carbazole hydrobromide in the MXene nanosheet suspension is 0.8-1.2 mmol / L.
6. The preparation method according to claim 4, characterized in that, The molar ratio of 4,4',4''-tris(carbazole-9-yl)triphenylamine to N-(2-aminoethyl)carbazole hydrobromide is 1:(0.8-1.2).
7. The preparation method according to claim 4, characterized in that, The voltage range of the cyclic voltammetric electropolymerization is -0.5~1.2V, the scan rate is 80-120mV / s, and the number of cycles is 2-10.
8. An electrochemical sensor, characterized in that, It includes an electrode substrate and a sensitive membrane disposed on the surface of the electrode substrate, wherein the sensitive membrane is a polymer composite film as described in any one of claims 1-3.
9. An electrochemical detection method for nitrophenol isomers, characterized in that, The nitrophenol isomers include at least one of ortho-nitrophenol, m-nitrophenol, and p-nitrophenol; the electrochemical detection method includes the following steps: A three-electrode system is used, with the electrochemical sensor described in claim 8 as the working electrode and the sample to be tested as the electrolyte. After potential enrichment, the nitrophenol isomer in the sample to be tested is detected by differential pulse voltammetry.
10. The electrochemical detection method according to claim 9, characterized in that, The samples to be tested include environmental water samples; And / or, the enrichment potential of the potential enrichment is -1.0 to -0.5V; And / or, the enrichment time for the potential enrichment is 120-180 s.
Citation Information
Patent Citations
MXene / polymer composite material as well as preparation method and application thereof
CN111518353A
Ionic type conjugated microporous polymer nano-channel composite membrane as well as preparation method and application thereof
CN118756155A
